Oz and the musical: The American art form and the reinvention of the American fairy tale. Issue 1 (1st March 2015) - Bunch, Ryan
Much as the musical is touted as an American art form, L. Frank Baum's The Wizard of Oz (1900) has been called the American fairy tale. Since its publication, the book has been eclipsed in popularity by a series of musical–theatrical adaptations, which are also among the most popular shows in the canon of musicals, suggesting an affinity between musicals and Oz. Close analysis of four Oz musicals, the Broadway extravaganza of 1903, the MGM film of 1939, The Wiz (1975) and Wicked (2003) shows how the conventions of musical theatre translate the already powerful symbolic national mythology of Baum's book into participatory expressions of American identity through embodied performance. In return, Oz gives the musical a signal national text which, through adaptation, allows the musical to reassert its own American pedigree while rearticulating the meaning of American identity at significant moments in the history of the genre.